Conditions of Entrepreneurship on the Example of Vineyards in the Moldova Region (Romania) and the Lower Silesia Voivodeship (Poland) - Izabela A. KWIL; Jacqueline A. ROWIECKA (Communications of International Proceedings, 2021)
The presented article aims to approximate the issues related to the determinants of entrepreneurship. The study covered enterprises located in the Lower Silesia Voivodship (Poland) and the Moldova Region (Romania), producing wine from their grapevines. The methodology of individual depth interviews was conducted among eight entrepreneurs: four of each from Poland and Romania. The undertaken research analysis showed that the selected determinants of entrepreneurship presented in this paper have a significant impact on entrepreneurship development in both described regions.
Keywords: Entrepreneurship; Lower Silesia Voivodeship; Moldova; Enotourism